Asymmetric Friedel–Crafts Alkylation Reaction in the Construction of Trifluoromethylated All-Carbon Quaternary Stereocenters - Wu, Hao; Liu, Ren-Rong; Jia, Yi-Xia (Synlett, 2014)
Construction of all-carbon quaternary stereocenter by asymmetric Friedel–Crafts alkylation reaction remains a significant challenge. By the introduction of CF3 group at the β-position of nitroalkene, a highly enantioselective Friedel–Crafts reaction of indoles with β-CF3-β-substituted nitroalkenes was achieved using Ni(ClO4)2-bisoxazoline complex as a catalyst, which afforded indole-bearing chiral compounds with trifluoromethylated all-carbon quaternary stereogenic centers in good yields and excellent enantioselectivities.
Keywords: alkylation; asymmetric catalysis; fluorine; indole; nickel